Goji Berries Supplementation in the Diet of Rabbits and Other Livestock Animals: A Mini-Review of the Current Knowledge - Agradi, Stella; Draghi, Susanna; Cotozzolo, Elisa; Barbato, Olimpia; Castrica, Marta; Quattrone, Alda; Sulce, Majlind; Vigo, Daniele; Menchetti, Laura; Ceccarini, Maria Rachele; Andoni, Egon; Riva, Federica; et al. (Frontiers in Veterinary Science, 2022)
In the last decades, several nutraceutical substances have received great attention for their potential role in the prevention and treatment of different diseases as well as for their beneficial effects in promoting the health of humans and animals. Goji berries (GBs) are the fruit of Lycium barbarum and other species of Lycium, used in the traditional Chinese medicine, which recently are becoming very popular in the Occidental world because of their properties, such as anti-aging, antioxidant, anticancer, neuroprotective, cytoprotective, antidiabetic, anti-inflammatory activities. These effects are essentially evaluated in clinical trials in humans, in experimental animal models, such as mice and rats, and in cell lines in in vitro studies. Only recently has scientific research evaluated the effects of GBs diet supplementation in livestock animals, including rabbits. Although studies in the zootechnical field are still limited and the investigation of the GB mechanisms of action is in an early stage, results are encouraging. This review includes a survey of the experimental trials that evaluated the effects of the GBs supplementation on reproductive and productive performances, immune system, metabolic homeostasis, and meat quality principally in the rabbit with also some references to other livestock animal species. Evidence supports the idea that the GBs supplementation could be used in rabbit breeding, although future studies should be conducted to establish the optimal dose to be administered and to assess the sustainability of the use of GBs in the diet of the rabbit.